DOES THE RANK-SIZE RULE MATTER IN INDONESIA? DETERMINANTS OF THE SIZE DISTRIBUTION OF CITIES - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2010)
In Indonesia the cities have continously grown. However they varied in size. Some cities have the population above two million citizens, while some have below than fIVe hundred thousands. Some economic factors are hypothesized to influence such distribution. This study aims to test the rank-size rule (Zipf's law) and to find the determinants of size distribution of cities. The panel data method is employed to satisfy the objectives of study. All district and provincial level data are usedfor year 1995, 2000 and 2005. The pareto exponent shows that the rank-size rule does not matter in Indonesia. Level of agglomeration economies, local government expenditure and number of administrative city increases the concentration of size of cities. The labor force participation and region's openness affects the size of cities to be more equally distributed Keywords: cities, rank-size rule, Zipf's law, pareto exponent, panel data